Short-Scale Photon-Phonon Interactions - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2018)
Using photon-phonon interactions, we experimentally demonstrate the storage of 200ps-long optical pulses for over 70 pulse widths. We moreover show that this concept is suitable for the non-reciprocal storage at multiple optical wavelengths.
CRIS-Team Scopus Importer:2021-06-29